The process of SME internationalization: British firms entering Brazil - Child, John; Rodrigues, Suzana Braga (Revista Economia & Gestão, 2008)
This paper examines the experience of thirty-two British SMEs that have entered the Brazilian market or, in a few cases, are still attempting to do so. It aims to discuss the factors that triggered those firms’ interest in Brazil and the process of their engagement with the Brazilian market. This allowed the identification of different types of export process and the factors giving rise to each type. Comparisons are also made with the insights offered by current literature. The findings suggest that the recent interest in the use of networking by SMEs is fully justified, and they also support the view that attention should be paid to the role of chance encounters. Trust-based relationships were fundamentally important in the internationalization process of the SMEs. From a resource-based perspective, it was evident that, in a culturally and institutionally distinctive business environment such as Brazil’s, technical superiority was a necessary condition, but not sufficient for successful export. Relationshipbuilding competencies were also required. The examination of the forms of relationship between companies and their customers in Brazil revealed three forms of transactional chain and factors associated with their use.